Integração de dados geofísicos e geológicos na caracterização morfológica de ocorrência de cobre na borda norte da Bacia do Camaquã (RS) - Côrtes, Ariane Raissa Pinheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In a scenario where the discovery of high tonnage and low volume deposits are increasingly scarce through geochemical prospecting and geological detailing of the surface, current and future perspectives in mineral exploration should consider the increasing use of geophysical methods as a fundamental tool for research of deep deposits, not susceptible to the action weathering processes. This work shows the results of the joint application of DC resistivity and induced polarization methods integrated with geological and structural data in potentially mineralized area with copper sulfides, located on the northern edge of the Camaquã Basin (RS). This mineral occurrence is hosted in silicified and fractured metarenite, characterized by the abundant presence of malachite and azurite as disseminations or impregnations in the rock weakness planes. Six lines were acquired in a Wenner-Schlumberger arrangement through the electrical imaging technique, with 510 m length for each row and spacing of 10 m between electrodes. The structural survey included mainly measures of fractured metarenites of Passo da Promessa Formation (Maricá Group) and Vacacaí metamorphic Complex's quartzites. The low sulphidation epithermal model is adopted as analogous to the mineralization, considering the relationship with the geological and geophysical data obtained for the area, in the absence of chemical analysis of soil or rock. The results indicate a low resistivity and high chargeability zone at 60 m depth associated with a sulphide zone with 100 m of length and elongated in the direction N55W. High resistivity and low chargeability zones are surrounding the sulphide zone, which are related to silicification areas. Finally, zones presenting medium to high resistivity and high chargeability indicate continuity at depth of the silicified metarenite of the mineral occurrence, with gradatively higher concentrations of metallic sulfides toward the sulphide zone. The...

Em um cenário onde a descoberta de depósitos de alta tonelagem e baixo volume é cada vez mais escassa por meio de prospecção geoquímica e detalhamento geológico de superfície, as perspectivas atuais e futuras na prospecção mineral devem considerar o uso crescente de métodos geofísicos como ferramenta fundamental para a pesquisa de depósitos profundos, não susceptíveis a ação de processos intempéricos. Este trabalho apresenta os resultados da aplicação conjunta dos métodos da eletrorresistividade e da polarização induzida integrados a dados geológico-estruturais em área potencialmente mineralizada com sulfetos de cobre, localizada na borda norte da Bacia do Camaquã (RS). Esta ocorrência mineral está alojada em metarenito silicificado e fraturado, caracterizada pela presença abundante de malaquita e azurita sob a forma de disseminações ou impregnações nos planos de fraqueza da rocha. Foram realizadas 6 linhas em arranjo Wenner-Schlumberger por meio da técnica de imageamento elétrico, de 510 m de comprimento cada e 10 m de espaçamento entre eletrodos. O levantamento estrutural englobou principalmente medidas de fraturas dos metarenitos da Formação Passo da Promessa (Grupo Maricá) e quartzitos do Complexo Metamórfico Vacacaí. O modelo epitermal de baixa sulfetação é adotado como análogo à mineralização, diante da relação com os elementos geológicos e geofísicos obtidos para a área, na ausência de análises químicas em solo ou rocha. Os resultados indicam uma zona de baixa resistividade e alta cargabilidade a 60 m de profundidade, relacionada a uma zona de sulfetação com 100 m de comprimento e alongada na direção N55W. Zonas de elevada resistividade e baixa cargabilidade delineiam um corpo circundante à zona de sulfetação, correlacionados com áreas de silicificação. Por fim, zonas com valores médios a altos de resistividade e altos de cargabilidade apontam a continuidade em profundidade...
Keywords: Geophysics; Geofisica; Cobre; Geologia estrutural